Influence of Principals’ Perception of Computers on Their Use in Administration of Public Secondary Schools in Kiambu County, Kenya - Samuel N. Njathi; Boniface Ngaruiya; Paul Maithya (European Scientific Journal, ESJ, 2018)
This paper is a report of a study carried out to establish the relationship that existed between principals’ Perception towards computer application and the actual computer use by principals in public secondary schools in Kiambu County. Computer use in schools administration is a contemporary issue in the improvement of quality leadership in schools. The study was triggered by the need for effective leadership in schools which would lead to improved academic performance in Kiambu County, a county surrounding the Kenyan capital city of Nairobi.. The study adopted descriptive survey research design. The target population for this study was 307 principals of public secondary schools in Kiambu County. The study sample comprised of 205 principals which translated to 67% of the target population. Simple randomand purposive sampling techniques were used in the selection of the respondents. A questionnaire was used for data collection. Relationship between the two variables under study was established by use of spearman rho. Descriptive statistics and Pearson’s Chi- square test of independence through the Statistical Package for Social Sciences (SPSS) were used to test the null hypotheses. The study found out that principal’s attitude towards use of computers influenced the use of computers among school principals. The study recommended that the MOE in collaboration TSC to mount regular ICT workshops to sensitize school principals on the need to use computers in school administration with a view of changing their attitudes towards computer use.